2017
DOI: 10.19082/4274
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of epidural analgesia among pregnant women in Jeddah, Saudi Arabia

Abstract: Background and objectiveLabor pain is one of the most severe forms of pain that women experience throughout their lifetime. Many pregnant women decide to have an epidural anesthesia to cope with labor pain. This study has focused on general awareness about epidural anesthesia among pregnant women in Jeddah, Saudi Arabia.MethodsThis was a cross-sectional hospital-based study using a self-administered questionnaire, conducted in King Faisal Specialist Hospital and Research Center and International Medical Centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 1 publication
5
24
3
Order By: Relevance
“…In our study, the labor pain was evaluated during labor at 5 stages and the pain scores were significantly lower in parturients who received epidural analgesia than those who did not (Table 2), and corresponding incidence rate of PPD is relatively lower. In this study, although remifentanil could rapidly cross the placenta into the fetal circulation, we did not use remifentanil for the method of application of women, help parturients establish confidence in natural labor, improve the rate of natural childbirth, reduce the adverse effects of pain on mother and baby, increase the rate of eutocia, increase blood flow to the placenta, improve fetal oxygen supply, relieve adverse reaction of labor pain, reduce or eliminate the parturients' childbirth pain, reduce maternal unnecessary physical consumption, maintain the dignity of parturients' childbirth, and let parturients enjoy the joy of child labor [30][31][32]. e overall painless labor analgesia rate of this study was 62.17%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the labor pain was evaluated during labor at 5 stages and the pain scores were significantly lower in parturients who received epidural analgesia than those who did not (Table 2), and corresponding incidence rate of PPD is relatively lower. In this study, although remifentanil could rapidly cross the placenta into the fetal circulation, we did not use remifentanil for the method of application of women, help parturients establish confidence in natural labor, improve the rate of natural childbirth, reduce the adverse effects of pain on mother and baby, increase the rate of eutocia, increase blood flow to the placenta, improve fetal oxygen supply, relieve adverse reaction of labor pain, reduce or eliminate the parturients' childbirth pain, reduce maternal unnecessary physical consumption, maintain the dignity of parturients' childbirth, and let parturients enjoy the joy of child labor [30][31][32]. e overall painless labor analgesia rate of this study was 62.17%.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,16,17 In Saudi Arabia, Gari et al found that older age, prior exposure to EA, attitudes towards EA were significant factors predicting the use of EPA among Saudi pregnant women in Jeddah. 4 Currently, there are no similar studies in Jazan region, Saudi Arabia; therefore, this study aims to evaluate the knowledge and attitudes towards EA in a sample of pregnant women from Jazan, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…If administered timely, EA relives about 90% to 95% of the labor pain, depending on type of medication and quantity . 4 Little is known about pregnant women's awareness of EA use during labor. 5,6 Studies from different parts of the world showed gaps in the knowledge and attitudes of pregnant women towards EA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations